Global security cultures - Kaldor, Mary (Polity Press, 2018)
Defining four main types - geo-politics, new wars, the liberal peace, and the war on terror she investigates how we might identify contradictions, dilemmas and experiments in contemporary security cultures that might ultimately open up new pathways to rescue and safeguard civility in the future. In this book, renowned scholar of war and human security Mary Kaldor introduces the concept of global security cultures in order to explain why we get stuck in particular pathways to security.